THE INTEGRATION OF INDUSTRY 4.0 AND LEAN TECHNOLOGIES IN MANUFACTURING INDUSTRIES: A SYSTEMATIC LITERATURE REVIEW - Bhanu Prakash Sah; Nadia Islam Tanha; Md Arafat Sikder; S M Habibullah (International Journal of Management Information Systems and Data Science, 2024)
This systematic literature review examines the integration of Industry 4.0 and Lean technologies in manufacturing, a topic of growing importance as industries seek to enhance efficiency and competitiveness. By analyzing 156 peer-reviewed journal articles, conference papers, and industry reports published between 2010 and 2023, this review identifies vital themes, benefits, challenges, and gaps in the literature. Industry 4.0, characterized by IoT, big data analytics, artificial intelligence (AI), and machine learning (ML), offers significant potential for improving real-time data collection, process automation, and advanced analytics. When integrated with Lean manufacturing principles, which focus on waste reduction and continuous improvement, these technologies can lead to more efficient operations, better quality control, and faster response times. However, the review also highlights several challenges, including high initial costs, the need for a skilled workforce, and the complexity of integrating new technologies with existing systems. Despite these challenges, numerous case studies and best practices demonstrate the successful implementation of these integrated approaches, providing valuable insights for future research and practical applications. This review concludes with recommendations for addressing the identified gaps and leveraging the synergies between Industry 4.0 and Lean technologies to achieve operational excellence in manufacturing.